Apply division algorithm to find the quotient q(x) and remainder r(x) on dividing f(x) by g(x) in each of the following:
(i) f(x) = x3 – 6x2 + 11x – 6, g(x) = x2 + x + 1
(ii) f(x) = 10x4 + 17x3 – 62x2 + 30x – 105, g(x) = 2x2 + 7x + 1
(iii) f(x) = 4x3 + 8x2 + 8x + 7, g(x) = 2x2 – x + 1
(iv) f(x) = 15x3 – 20x2 + 13x – 12, g(x) = x2 – 2x + 2
(i) f(x) = x3 – 6x2 + 11x – 6 and g(x) = x2 + x + 1
(ii) f(x) = 10x4 + 17x3 – 62x2 + 30x – 105, g(x) = 2x2 + 7x + 1
(iii) f(x) = 4x3 + 8x2 + 8x + 7, g(x) = 2x2 – x + 1
(iv) f(x) = 15x3 – 20x2 + 13x – 12, g(x) = x2 – 2x + 2
Check whether the first polynomial is a factor of the second polynomial by applying the division algorithm:
(i) g(t) = t2 – 3; f(t) = 2t4 + 3t3 – 2t2 – 9t – 12
(ii) g(x) = x2 – 3x + 1; f(x) = x5 – 4x3 + x2 + 3x + 1
(iii) g(x) = 2x2 – x + 3; f(x) = 6x5 − x4 + 4x3 – 5x2 – x – 15
(i) g(t) = t2 – 3; f(t) = 2t4 + 3t3 – 2t2 – 9t – 12
g(t) = t2 – 3g(t) = t2 – 3 f(t) = 2t4 + 3t3 – 2t2 – 9t Therefore, g(t) is the factor of f(t).
(ii) g(x) = x2 – 3x + 1; f(x) = x5 – 4x3 + x2 + 3x + 1
g(x) = x2 – 3x + 1 g(x) = x2 – 3x + 1 f(x) = x5 – 4x3 + x2 + 3x + 1.Therefore, g(x) is not the factor of f(x).
(iii) g(x) = 2x2 – x + 3; f(x) = 6x5 − x4 + 4x3 – 5x2 – x – 15
g(x) = 2x2 – x + 3 g(x) = 2x2 – x + 3 f(x) = 6x5 − x4 + 4x3 – 5x2 – x – 15
Obtain all zeroes of the polynomial f(x) = f(x) = 2x4 + x3 – 14x2 – 19x – 6, if two of its zeroes are -2 and -1.
f(x) = 2x4 + x3 – 14x2 – 19x – 6
If the two zeroes of the polynomial are -2 and -1, then its factors are (x + 2) and (x + 1)
(x + 2)(x + 1) = x2 + x + 2x + 2 = x2 + 3x + 2
f(x) = 2x4 + x3 – 14x2 – 19x – 6 = (2x2 – 5x – 3)(x2 + 3x + 2)
= (2x + 1)(x – 3)(x + 2)(x + 1)
Therefore, zeroes of the polynomial = - 1/2, 3, -2 , -1
Obtain all zeroes of f(x) = x3 + 13x2 + 32x + 20, if one of its zeroes is -2.
f(x) = x3 + 13x2 + 32x + 20
Since, the zero of the polynomial is -2 so, it means its factor is (x + 2).
So, f(x) = x3 + 13x2 + 32x + 20 = (x2 + 11x + 10)(x + 2)
= (x2 + 10x + x + 10)(x + 2)
= (x + 10)(x + 1)(x + 2)
Therefore, the zeroes of the polynomial are – 1, – 10, – 2.
Obtain all zeroes of the polynomial f(x) = x4 – 3x3 – x2 + 9x – 6, if the two of its zeroes are – √3 and √3.
f(x) = x4 – 3x3 – x2 + 9x – 6 Since, two of the zeroes of polynomial are -√3 and √3 so,(x + √3)(x – √3) = x2– 3x2 – 3
So, f(x) = x4 – 3x2 – x2 + 9x – 6 = (x2 – 3)(x2 – 3x + 2)
= (x + √3)(x – √3)(x2– 2x – 2 + 2)
= (x + √3)(x – √3)(x – 1)(x – 2)
Therefore, the zeroes of the polynomial are - √3, √3, 1, 2.
Obtain all zeroes of the polynomial f(x) = 2x4 – 2x3 – 7x2 + x – 1, if the two of its zeroes are – √(3/2) and √(3/2).
f(x) = 2x4 – 2x3 – 7x2 + x – 1 Since, - √(3/2) and √(3/2) are the zeroes of the polynomial, so the factors are
So, f(x) = 2x4– 2x3–7x2+ x – 1
Therefore, the zeroes of the polynomial = x = -1, 2, -√(3/2) and √(3/2).
Find all the zeroes of the polynomial x4 + x3 – 34x2 – 4x + 120, if the two of its zeroes are 2 and – 2.
x4 + x3 – 34x2 – 4x + 120 Since, the two zeroes of the polynomial given is 2 and – 2 So, factors are (x + 2)(x – 2) = x2 + 2x – 2x – 4 = x2 – 4x2 – 4
So, x4 + x3 – 34x2 – 4x + 120 = (x2 – 4)(x2 + x – 30)
= (x – 2)(x + 2)(x2 + 6x – 5x – 30)
= (x – 2)(x + 2)(x + 6)(x – 5)
Therefore, the zeroes of the polynomial = x = 2, – 2, – 6, 5
Find all the zeroes of the polynomial 2x4 + 7x3 – 19x2 – 14x + 30, if the two of its zeroes are √2 and - √2.
2x4 + 7x3 – 19x2 – 14x + 302 Since, √2 and-√2 are the zeroes of the polynomial given. So, factors are (x + √2) and (x - √2)
= x2+√2x – √2x – 2 = x2 – 2
So, 2x4 + 7x3 – 19x2 – 14x + 30 = (x2 – 2)(2x2 + 7x – 15)
= (2x2+ 10x – 3x – 15)(x + √2)(x – √2)
= (2x – 3)(x + 5)(x + √2)(x – √2)
Therefore, the zeroes of the polynomial is √2,- √2,-5, 3/2.
Find all the zeroes of the polynomial f(x) = 2x3 + x2 – 6x – 3, if two of its zeroes are – √3 and √3.
f(x) = 2x3 + x2 – 6x – 3 Since, -√3 and √3 are the zeroes of the given polynomial So, factors are (x - √3) and (x + √3)
= (x2– √3x + √3x – 3) = (x2 – 3)
So, f(x) = 2x3 + x2 – 6x – 3 = (x2 – 3)(2x + 1)
= (x – √3)(x + √3)(2x + 1)
Therefore, set of zeroes for the given polynomial = √3,– √3, –1/2
Find all the zeroes of the polynomial f(x) = x3 + 3x2 – 2x – 6, if the two of its zeroes are √2 and - √2.
f(x) = x3 + 3x2 – 2x – 6 Since, √2 and -√2 are the two zeroes of the given polynomial. So, factors are (x + √2) and (x - √2)
= x2+ √2x – √2x – 2 = x2 – 2
By division algorithm, we have:
f(x) = x3 + 3x2 – 2x – 6 = (x2 – 2)(x + 3)
= (x – √2)(x + √2)(x + 3)
Therefore, the zeroes of the given polynomial is - √2, √2 and – 3.
What must be added to the polynomial f(x) = x4 + 2x3 – 2x2 + x − 1 so that the resulting polynomial is exactly divisible by g(x) = x2 + 2x − 3.
f(x) = x4 + 2x3 – 2x2 + x − 1
We must add (x – 2) in order to get the resulting polynomial exactly divisible by g(x) = x2 + 2x − 3.
What must be subtracted from the polynomial f(x) = x4 + 2x3 – 13x2 –12x + 21 so that the resulting polynomial is exactly divisible by g(x) = x2 – 4x + 3.
f(x) = x4 + 2x3 – 13x2 – 12x + 21
We must subtract (2x – 3) in order to get the resulting polynomial exactly divisible by g(x) = x2 – 4x + 3.
Given that √2 is a zero of the cubic polynomial f(x) = 6x3+ √2x2– 10x – 4√2, find its other two zeroes.
f(x) = 6x3+√2x2 – 10x – 4√2 Since, √2 is a zero of the cubic polynomial So, factor is (x–√2)
Given that x – √5 is a factor of the cubic polynomialfind all the zeroes of the polynomial.
In the question, it’s given that x – √5 is a factor of the cubic polynomial.
So, the zeroes of the polynomial